PENDAMPINGAN UMKM ACTIVE SPORTS: IMPLEMENTASI STRATEGI PEMASARAN MELALUI MEDIA SOSIAL DAN BRANDING - Moh. Ainul Fais; I Gusti Ayu Sri Deviyanti; Nyoman Sri Widari; Wiwik Prihartanti; Agus Rahmanto (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
In order to increase sales optimization and sales through the implementation of a social media-based strategy for branding MSME Active Sports, assistance was carried out as a community service target held by the Surabaya Integrated Science & Technology Institute, WR Supratman University Surabaya, and Dharma Cendika Catholic University Surabaya. Increasingly tight market competition in the swimming equipment and equipment market, MSME Active Sports requires an innovative marketing approach. This community service activity includes creating logos, business cards, Instagram accounts and Linktree to build branding for MSME Active Sports. Marketing via social media is a means of supporting the promotion of Active Sports MSMEs with the hope of expanding market reach and attracting new customers. The results of this community service activity are expected to be able to increase the optimization of sales of MSME Active Sports products and at the same time strengthen a profitable position in market competition. Through this assistance, it is hoped that Active Sports MSMEs will be able to optimize digital marketing strategies and build sustainable branding.